Cantigas de ninar do nordeste brasileiro (Paraíba e Pernambuco): uma abordagem semiótico-discursiva - Carvalho, Maria José Lima de (2020)
This work was motivated by studies that we did in works about lullabies, starting with Cancioneiro da Paraíba (SANTOS; BATISTA, 1993), when we realized the need to carry out a thesis on the subject that aimed to analyze the present value systems in lullabies, exploring the thematic-figurative categories of discursivization in the light of the semiotics of cultures. Therefore, our problem was to discover if lullabies were used like popular practices among the modern families and what kind of lullabies were used in this practice.We started from a substantial data collect of popular and / or erudite songs that we made in regions of Paraíba and Pernambuco and that served as corpus to this thesis, allowing the encounter of texts from different times and places, using the criterion of the song’s functionality, that is, those used to help children's sleep. Traditionally, they are known as lullabies, soothe, lull, because they are sung in activities that characterize the mother’s care and affection with her little son, before putting him to sleep. Our data collect reveals that traditional songs and / or adaptations, already disseminated by other researches or unpublished texts, which are materialized by narratives sung or dialogued, by discourses that indicate knowledge about the world and what conceptions are raised about it. Themes and actors vary, but family figures prevail. In this expressive universe and through the relevance of gender as a portal of traditions, superstitions, beliefs, our research is inserted, which used the French Semiotics as a theoretical basis, considering, among other theorists, Greimas and Courtés (2012), Pais (1993), Batista (2014), to support the analysis of this corpus. We group our survey by informants and researched communities, organizing these songs into seven thematic-figurative categories, since, although they are songs used in a single social function: to calm down, they belong to different discursive genres, such as narrative poetry, myths, tales , parlendas and even popular songs, they are not usually used as cherish.